PENGARUH KEPEDULIAN TERHADAP MASA DEPAN PADA PERILAKU KONSUMEN HIJAU - Try Rahma Sari; Elvani Anisa Putri; Dewi Kurniaty (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to analyze the influence of concern for the future on green consumer behavior. The type of research used is quantitative research derived from a sample of people or residents. Data collection using questionnaire disseminator technique with a total sample of 106 people. The analysis tool used is correlation test analysis. The results of this study are: (1) concern for the future has a significant influence on the value of green consumption, (2) concern for the future has a significant effect on consumer behavior (3) concern for the future has a significant influence on prosocial attitudes. This shows that concern for the future has had a positive and significant influence on the value of green consumption, consumer perception, and prosocial attitudes